2017
DOI: 10.1186/s40168-017-0368-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predictive features of Clostridium difficile infection recurrence before, during, and after primary antibiotic treatment

Abstract: BackgroundColonization by the pathogen Clostridium difficile often occurs in the background of a disrupted microbial community. Identifying specific organisms conferring resistance to invasion by C. difficile is desirable because diagnostic and therapeutic strategies based on the human microbiota have the potential to provide more precision to the management and treatment of Clostridium difficile infection (CDI) and its recurrence.MethodsWe conducted a longitudinal study of adult patients diagnosed with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 50 publications
3
23
0
1
Order By: Relevance
“…Examination of intestinal bacterial populations of CDI patients and their correlation with previous antibiotic treatment, showed that there was no phylum-and family-level composition common to all CDI patients, as has been described in other studies [21][22][23]. In their study comparing the gut microbiome pro le of CDI versus non-CDI patients, Manges et al found an increase in Firmicutes, Proteobacteria and Actinobacteria phyla, as well as a decrease in Bacteroidetes [24].…”
Section: Discussionmentioning
confidence: 72%
“…Examination of intestinal bacterial populations of CDI patients and their correlation with previous antibiotic treatment, showed that there was no phylum-and family-level composition common to all CDI patients, as has been described in other studies [21][22][23]. In their study comparing the gut microbiome pro le of CDI versus non-CDI patients, Manges et al found an increase in Firmicutes, Proteobacteria and Actinobacteria phyla, as well as a decrease in Bacteroidetes [24].…”
Section: Discussionmentioning
confidence: 72%
“…Thus, weak connectivity of the patient gut bacterial community after FMT was an indicator that the patient was more likely to relapse. Prior efforts to predict C. difficile relapse from the microbiome did not find post-FMT indicators of relapse, although connectivity was not previously considered (Pakpour et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…identified decreased Shannon diversity, depletion of Bacteroidetes and reduced abundance of Veillonella dispar by random forest models as being predictive of rCDI. 38 However, the predictive capability of their model was poor (AuROC=0.68). Although there were differences in the microbial characteristics identified, this was likely related to differences in patient populations between our studies.…”
Section: Discussionmentioning
confidence: 99%